PROFIL KOMPONEN FISIK PREDOMINAN DARI KONDISI FISIK ATLET GULAT JAWA BARAT PADA PON XVIII RIAU 2012 - Karima Akhlaqunnisa; Titing Nurhayati; Nova Sylviana; Ambrosius Purba; Panji Fortuna Hadisoemarto (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2018)
During the National Sports Week XVIII held in September 2012, wrestling athletes from West Java Province could not meet the expected performance; since they got only one gold and two bronze medals. The athlete’s performance usually affected by three factors; physical condition, technique, and mental condition. To achieve the best result, the gold medal, athletes should have good predominant physical condition indicators, such as muscle strength, endurance, power, and flexibility. The purpose of this study is to know the physical condition of West Java’s wrestling athletes in the National Sports Week XVIII. The method used was a cross-sectional descriptive study using secondary data obtained from the Sports Medicine Department of the National Sports Committee of Indonesia in Bandung. The data are chosen from the predominant physical condition indicator explained before, along with cardio-respiratory endurance. After that, we compared the data we obtained with the National Sports Committee of Indonesia’s standards and categorized it specific type; less, enough, good, very good, and perfect. Male and female athletes had different category systems. After analysis, we found that several predominant physical components of wrestling athletes of West Java Province in National Sports Week XVIII had not met the requirement for the good and perfect category andneeded to be improved. In conclusion, athletes should be able to get a gold medal if their predominant physical component achieves the good and perfect category.